Kasih sebagai Pengalaman akan Allah dalam Diri Santo Titus Brandsma - Kota, Ignasius Liberto Sando (Perspektif, 2025)
This study explores love as a transcendent experience of God in the life of Saint Titus Brandsma, often reduced to mere moral sentiment or social affection. Addressing the increasing secularization of the concept of love, this research re-examines its mystical dimension as both contemplative and active. The sentral question concerns how love can be lived as a personal encounter with God, and how this was manifested in Brandsma’s life, particularly amid suffering and resistance against totalitarian ideologies. The study employed a qualitative-descriptive method using a spiritual theological and phenomenological approach to religious experience, based on literature review of Titus’s writings, Church documents, and spiritual theology sources. The findings reveal that Brandsma perceived love as an integration of contemplation and concrete action, love that fosters a personal relationship with God and encourages engagement with suffering and social justice. Love, in this context, emerges not only as a virtue but as a transformative spiritual power rooted in deep faith. In conclusion, Brandsma’s understanding of love exemplifies a mystical-contemplative spirituality that remains relevant for the Church and contemporary society, offering a profound response to violence, hatred, and spiritual dryness in the modern world.